Study on Soil Water and Suction Stress Characteristics for Unsaturated Clay Soil of Airport Engineering Based on Laboratory Tests. (23rd July 2021) - Feng, Jun; Zhang, Guangze
Abstract : For the unsaturated soil in Feidong China, this study examined the suction stress characteristics based on the soil-water characteristic curve (SWCC), which was different from traditional research ideas. At the same time, the unsaturated consolidation device was adopted for SWCC tests, with consideration of the influence of yielding stress of soil, which was different from the traditional test approach of the soil-water characteristic curve. The results were estimated using the van Genuchten model, which was revealed that this is well-fit for the studied unsaturated soil, and the triaxial shear-strength tests were conducted with suction control. Then, the suction stress characteristic curve (SSCC) was analyzed, and SWCC-predicted data were compared with triaxial test-derived suction stress data. For the studied unsaturated soil, the deviatoric stress increased with the net inner stress p − u a at the same matric suction. At the same net inner pressure, the deviatoric stress increased with the matric suction, which verified the hardening activity of matric suction on the tested unsaturated soil strength. Besides, triaxial test-derived suction stress data greatly conformed to SWCC data-derived SSCC that was determined using identical parameters used in the SWCC model.